SEKOLAH SEBAGAI INSTRUMEN KONSTRUKSI SOSIAL DI MASYARAKAT - Prihatin, Nyimas Yunierti; Ismail, Fajri; Pratama, Irja Putra; Zulhijra, Zulhijra; Syarnubi, Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The availability of facilities in a school has an important role in the implementation of the educational process. Each school has a size and type, varies depending on the resources and goals of how the education provider. As an institution, school is a place to teach and learn students, a place to train and give instructions about a certain scientific field and skills to students. The existence of a place called a school is a building complex, consisting of a laboratory, physical facilities provided as a center for teaching and learning activities for teachers and students.Schools are institutions that carry out the formal education system, and have an important role in the socialization process, namely the process of helping individuals develop into social beings and beings who can adapt well in society. intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ). Schools have an important role in the socialization process, namely the process to help the development of individuals as social beings and beings who can follow the situation well in society.The real educational processes are the relationship of activities that take place in the classroom, school education can help students to gain the knowledge and skills needed to live, therefore one of the goals that must be achieved by education is to develop life skills. This is actually the direction of the competency-based curriculum, life skills education and broad-based education being developedAs a forum or institution where there has been a socialization process and teaching and learning process between educators and students. Schools must be able to provide a good interaction in printing the nation's next generation so that the social dynamics of the school become a miniature of the nation's social dynamics with dignity and character.